Efektivitas Pelayanan Perizinan Berusaha Berbasis Digital Di Kabupaten Bangli - I Dewa Oka Angga Wirama; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
The industrial revolution will change human lifestyles, as people interact with each other and work from manual to digital. The OSS RBA institution offers a variety of business licenses, including Electronically Integrated Business Licensing and Online Single Submission Risk Based Approach (OSS RBA). The OSS RBA system allows micro, small, medium and large business owners to apply for business licenses online. The formulation of the problem to be discussed is (1) How is the Implementation of Digital-Based Business Licensing at the Bangli Regency Investment and One-Stop Integrated Services Office? And (2) how are the obstacles and efforts made by the Bangli Regency One-Stop Investment and Integrated Services Office in streamlining digital-based business licensing services? This research uses interview techniques as part of an empirical legal research design. Business licensing is based on two laws and regulations: Government Regulation Number 5 of 2021 which regulates the implementation of risk-based licensing, and Government Regulation Number 6 of 2021 which regulates the implementation of regional licensing.